Iron deficiency anemia in women: solutions to the problem - Tikhomirov A.L; Sarsaniya S.I (LCC «Medicine-Inform», 2020)
A.L. Tikhomirov1, S.I. Sarsaniya2 1A.I. Evdokimov Moscow University of Medicine and Dentistry, Moscow, Russian Federation 2LLC "ANV", Moscow, Russian Federation Iron deficiencies and iron deficiency anemia remain an important clinical issue. This article discusses high prevalence of iron deficiency anemia and its consequences in women. Classification of iron deficiencies, etiology, and pathogenesis of iron deficiency are addressed. A special section is devoted to iron metabolism. The article provides a brief summary of major proteins involved in iron metabolism and their role in maintaining iron homeostasis. Functional role of hepcidin (which plays a critical role in the regulation of extracellular iron levels) and iron recirculation are highlighted. The most promising areas of hepcidin application in hematology are addressed. Diagnostic criteria for iron deficiency anemia are uncovered. This approach which includes modern diagnostic and treatment modalities for iron deficiency additionally help protect women's health even in common gynecological disorders and their complications associated with iron deficiency. Optimal dru g choice for the treatment and prevention of iron deficiency anemia is an important research area in modern clinical medicine. Keywords: iron deficiency anemia, iron, hepcidin, transferrin, erythropoietin, abnormal uterine bleeding, iron-containing biomolecules, complex iron medications. For citation: Tikhomirov A.L., Sarsaniya S.I. Iron deficiency anemia in women: solutions to the problem. Russian Journal of Woman and Child Health. 2020;3(1):-50. DOI: 10.32364/2618-8430-2020-3-1-44-50.